2021
DOI: 10.1002/hep.31798
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Effective Albumin in Patients With Decompensated Cirrhosis: Clinical and Prognostic Implications

Abstract: Background & Aims. Circulating albumin in cirrhosis can be dysfunctional due to accumulating structural damages, leading to the concept of effective albumin concentration (eAlb) referring to the albumin portion presenting structural and functional integrity. We aimed to estimate eAlb in patients with decompensated cirrhosis and analyze its relationships with albumin function and clinical outcomes as compared to total albumin concentration (tAlb). Approach & Results. We evaluated 319 cirrhotic patients hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…In patients with decompensated cirrhosis, serum albumin shows structural abnormalities, most often involving reversible oxidation and glycation [ 35 ], which lead to impaired binding capacity in albumin and increased risk of liver failure [ 36 ]. By combining liquid chromatography-electrospray ionization-mass spectrometry and standard methods of albumin determination, ‘effective’ albumin has been defined as the albumin isoform presenting structural and functional integrity as differentiated from ‘total’ albumin, which includes modified albumin.…”
Section: Bio-mechanistic Relationship Between Hypoalbuminemia and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with decompensated cirrhosis, serum albumin shows structural abnormalities, most often involving reversible oxidation and glycation [ 35 ], which lead to impaired binding capacity in albumin and increased risk of liver failure [ 36 ]. By combining liquid chromatography-electrospray ionization-mass spectrometry and standard methods of albumin determination, ‘effective’ albumin has been defined as the albumin isoform presenting structural and functional integrity as differentiated from ‘total’ albumin, which includes modified albumin.…”
Section: Bio-mechanistic Relationship Between Hypoalbuminemia and Infectionmentioning
confidence: 99%
“…By combining liquid chromatography-electrospray ionization-mass spectrometry and standard methods of albumin determination, ‘effective’ albumin has been defined as the albumin isoform presenting structural and functional integrity as differentiated from ‘total’ albumin, which includes modified albumin. Most importantly, it has been suggested that serum levels of ‘effective’ albumin may be a better prognostic indicator than ‘total’ albumin in patients with decompensated cirrhosis [ 36 ].…”
Section: Bio-mechanistic Relationship Between Hypoalbuminemia and Infectionmentioning
confidence: 99%
“…Protein restriction is not systematically advocated, as these patients usually tolerate a normal protein intake. Besides hypoalbuminemia, potentially requiring a higher protein intake, albumin glycation is present in T2D [ 193 ]. The structurally damaged albumin molecule is also dysfunctional, and albumin administration may be required to reduce ascites.…”
Section: Management Of Other Comorbidity In Patients With T2dmentioning
confidence: 99%
“…There have been attempts to define an effective albumin concentration based on albumin functionality and concentration, but such definitions involve effective albumin quantification using techniques not commonly available in the clinical setting, and the results likely vary by specific clinical conditions 14 . However, results of such investigations provide important insights into the structural abnormalities of circulating albumin that occur in patients with decompensated cirrhosis, which lead to decreases in effective albumin concentrations with disease progression 15 . Additionally, these studies of effective albumin concentrations confirm the results of previous findings demonstrating that exogenously administered albumin cannot be assumed to have the same properties as endogenous albumin produced by the liver, since commercially available albumin preparations are known to undergo posttranslational modifications 16 …”
Section: Commentmentioning
confidence: 99%